Realizing Minimum Service Standards for Food Based on Local Wisdom in Central Halmahera Regency - Abdurachman F., Maman (Sangia Research Media and Publishing, 2020)
Realizing minimum service standards in the food sector is the responsibility of the Government in general, and the Government of Central Halmahera Regency in particular. Various efforts have been made, among others, through the approach of implementing